Positive electrode slurry and preparation method thereof, positive electrode plate and preparation method thereof, and lithium ion battery

Through the positive electrode slurry with high viscosity and high solid content, the thick electrode preparation process is simplified and high surface density coating is realized, which solves the problems of complex process and poor electrochemical performance in the existing technology, and achieves the electrical performance of the thin electrode technology level and energy density.

CN119208604APending Publication Date: 2024-12-27BEIJING WELION NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411158748.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing thick electrode technology has complex preparation process, poor electrochemical performance, and difficult to meet market demand. The large number of existing additives has affected the performance of the battery cell.

Method used

Provide a high viscosity and high solids content of positive electrode slurry, including positive electrode active materials, fluorine-containing polyolefin-containing binders, amino and hydroxyl-containing compounds and conductive agents, and realize high-side density coating through simplified processes, using one-time Coating and preparing positive electrode sheets, compatible with single-layer coating technology.

Benefits of technology

The electrical performance of thick electrode sheets is achieved comparable to that of thin electrode technology, reducing process costs, simplifying the preparation process, and improving the energy density and capacity of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208604A_ABST
    Figure CN119208604A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of lithium batteries, and discloses positive electrode slurry and a preparation method thereof, a positive electrode plate and a preparation method thereof, and a lithium ion battery. The positive electrode slurry comprises a slurry effective component and a solvent, and the slurry effective component comprises a positive electrode active material, a first binder, a second binder and a first conductive agent; wherein the first binding agent is a fluorine-containing polyolefin binding agent; the second binder is a compound containing amino and hydroxyl; wherein the solid content of the positive electrode slurry is not lower than 68%, and the viscosity of the positive electrode slurry at 25 + / -2 DEG C is not lower than 100000 mPa.S. The positive electrode paste can simplify the preparation process of a thick pole piece, realize high-surface-density coating, improve the capacity of a battery cell and improve the energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery preparation, and in particular to a positive electrode slurry and a preparation method thereof, a positive electrode plate and a preparation method thereof, and a lithium ion battery. Background Art

[0002] In the power market, the energy density of lithium iron phosphate batteries has transitioned from 180Wh / kg to 220Wh / kg, and even to 240Wh / kg. The energy density of ternary batteries has transitioned from 360Wh / kg to 400Wh / kg, and some companies have even released 500Wh / kg products. Batteries with higher and higher energy density are favored by the vehicle market. In the energy storage market, the 280Ah square shell battery cells that started in 2022 have been upgraded to 314Ah, 330Ah, 340Ah, and even 560Ah in 2023. To achieve high energy density and high capacity batteries, the development of lithium iron phosphate thick electrode technology is imperative.

[0003] Most of the thick electrode technologies currently published are solved by double-layer and multi-layer coating. For example, CN115295799A discloses a positive electrode active material, a lithium iron phosphate thick electrode and its preparation method and application. In the invention, the positive electrode active material includes a specific primary rod-shaped lithium iron phosphate and a secondary spherical lithium iron phosphate generated from the primary rod-shaped lithium iron phosphate, and the two specific structures of lithium iron phosphate materials cooperate with each other. CN117525303A discloses the addition of single-walled carbon nanotubes, based on its larger aspect ratio, to achieve thick electrode production. CN115275109A discloses a lithium iron phosphate thick electrode, including a current collector and a first coating disposed on at least one side of the current collector. The first coating is also sequentially provided with a second coating and a lithium supplement layer on the side surface away from the current collector, etc., and a thick electrode is realized by a three-layer coating method. However, the double-layer and multi-layer coating methods are relatively complicated, and the technical maturity is relatively low, which is difficult to meet the rapidly developing market demand. CN114050260A discloses a positive electrode film additive composition and a positive electrode plate. The synergistic effect of a binder auxiliary, a charge stabilizer and a polymer superdispersant can improve the dispersibility of active materials and conductive substances, reduce the viscosity of the slurry, and solve the problem of cracking of thickly coated electrodes during thick coating. However, the patent has many types of additives, and there may be residues in the electrode after drying, which will have an adverse effect on battery performance such as battery capacity, battery efficiency, and battery cycle.

[0004] In summary, the existing thick electrode technology has a complex preparation process, and there is still a certain gap between the electrical performance of the thick electrode sheets produced by the thick electrode technology and the electrical performance of the electrode sheets produced by the thin electrode technology, which is difficult to meet market demand. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of complex preparation process and unsatisfactory electrochemical performance of thick electrode technology in the prior art, and to provide a positive electrode slurry and a preparation method thereof, a positive electrode plate and a preparation method thereof, and a lithium-ion battery. The positive electrode slurry can simplify the thick electrode plate preparation process, achieve high surface density coating, and improve the capacity of the battery cell.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a positive electrode slurry, wherein the positive electrode slurry comprises a slurry effective component and a solvent, wherein the slurry effective component comprises a positive electrode active material, a first binder, a second binder and a first conductive agent;

[0007] Wherein, the first binder is a fluorinated polyolefin binder; the second binder is a compound containing amino groups and hydroxyl groups;

[0008] The solid content of the positive electrode slurry is not less than 68%, and the viscosity at 25±2° C. is not less than 100,000 mPa·S.

[0009] The second aspect of the present invention provides a method for preparing the above-mentioned positive electrode slurry, comprising:

[0010] (1) The solvent includes a first solvent and a second solvent, and the first binder is dissolved in the first solvent to obtain a first adhesive solution;

[0011] (2) mixing a second binder, a second solvent and a first conductive agent to obtain a second adhesive solution;

[0012] Wherein, the first binder is a fluorinated polyolefin binder, and the second binder is a compound containing amino groups and hydroxyl groups;

[0013] (3) Mixing the first slurry, the second slurry and the positive electrode active material.

[0014] A third aspect of the present invention provides a positive electrode plate, comprising a current collector and an active coating layer disposed on the surface of the current collector, wherein the active coating layer is made of the positive electrode slurry described in the first aspect.

[0015] A fourth aspect of the present invention provides a method for preparing a positive electrode sheet, comprising: coating the positive electrode slurry described in the first aspect on the surface of a current collector, and then drying and rolling.

[0016] A fifth aspect of the present invention provides a lithium-ion battery, comprising the positive electrode sheet described in the third aspect or the positive electrode sheet prepared by the preparation method described in the fourth aspect.

[0017] Through the above technical solution, the present invention provides a high-viscosity, high-solid content positive electrode slurry, the thick electrode sheet produced by the invention has the same electrical performance as the electrode sheet produced by the thin electrode technology, and the gram capacity is equivalent, reaching the technical level of the thin electrode. At the same time, the positive electrode slurry can be used to prepare the positive electrode sheet by one-time coating, the process steps are simple, and it is compatible with the existing single-layer coating technology, without the need for complex coating processes, which is conducive to reducing process costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a morphology picture of the positive electrode sheet P1 prepared in Example 1 of the present invention;

[0019] Figure 2 This is a morphology picture of the positive electrode plate DP2 prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0020] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0021] The first aspect of the present invention provides a positive electrode slurry, the positive electrode slurry comprises a slurry effective component and a solvent, the slurry effective component comprises a positive electrode active material, a first binder, a second binder and a first conductive agent;

[0022] The first binder is a fluorinated polyolefin binder; the second binder is a compound containing amino groups and hydroxyl groups; the solid content of the positive electrode slurry is not less than 68%, and the viscosity at 25±2°C is not less than 100000 mPa·S.

[0023] In the present invention, "first" and "second" are only for the convenience of measurement and do not represent the order in which the components are mixed with the solvent. As long as the positive electrode slurry contains positive electrode active material, a first binder, a second binder, a first conductive agent and a solvent, and meets the above-mentioned solid content and viscosity ranges, it will be fine.

[0024] In the present invention, the solid content of the positive electrode slurry refers to the percentage of the total mass of solids in the positive electrode slurry to the total mass, and the testing method includes: taking 2-3g of the slurry, placing it in a solid content tester (Mettler-HX204), selecting the shutdown mode of 1mg / 90s, and the drift value of the test result meets the set value of 1mg / 90s, ending the test, and the displayed value is the solid content.

[0025] In the existing wet and dry homogenization technologies, the solid content of the positive electrode slurry is generally 50-65%, and the viscosity is below 10000mPa·S. In the present invention, the synergistic effect of the positive electrode active material, the first glue and the second glue is used to control the solid content of the slurry to be not less than 68%, and the viscosity to be not less than 100000mPa·S. The electrical properties of the thick electrode sheet made of the high viscosity and high solid content positive electrode slurry are equivalent to those of the electrode sheet made by the thin electrode technology, and the gram capacity is equivalent, reaching the technical level of the thin electrode.

[0026] According to some preferred embodiments of the present invention, the solid content of the positive electrode slurry is 68-85%, preferably 72-78%. In the above preferred case, it is beneficial to further achieve high surface density coating and improve the energy density of the battery cell.

[0027] The inventors of the present invention have found in their research that by introducing the first binder and the second binder to form a positive electrode slurry with a high solid content, the positive electrode slurry can meet the requirements of 470-600 g / m 2 The thick electrode sheet produced by this method has a higher peel strength, which is conducive to the stability of the electrode sheet surface density. The reason may be that under the synergistic effect of the above-mentioned specific components, each component has good dispersibility, especially the Brownian motion of the conductive agent particles is weak, so the positive electrode slurry formed can have higher stability.

[0028] According to some preferred embodiments of the present invention, the viscosity of the positive electrode slurry at 25±2° C. is 100,000-400,000 mPa·S, preferably 120,000-200,000 mPa·S.

[0029] In the present invention, the test method of the viscosity of the positive electrode slurry includes: at 25±2°C, 80mL of the positive electrode slurry is weighed in a 100mL beaker and placed under a rotational viscometer (Shanghai Lichen Technology Co., Ltd.-NDJ-9). The viscometer uses a No. 4 rotor with a rotation speed of 3rpm. The rotor scale line is inserted into the slurry to start testing the viscosity. When the numbers displayed on the viscometer are stable, the viscosity data is recorded.

[0030] According to some preferred embodiments of the present invention, the cone penetration of the positive electrode slurry is not less than 30 mm, preferably 30-50 mm, and more preferably 32-35 mm.

[0031] In the present invention, "cone penetration" refers to the hardness of the slurry. Controlling the cone penetration of the slurry within the above preferred range is conducive to achieving high surface density coating and further improving the capacity of the battery cell. In the present invention, the cone penetration is tested using a SZR3 cone penetration meter. The specific test method is to place a tank filled with slurry under the cone of the cone penetration meter at a temperature of 25±2°C, and let the cone fall freely into the tank. Immediately read the corresponding number on the standard ruler, and the depth of the corresponding cone into the slurry is the cone penetration.

[0032] In the present invention, the selection range of the positive electrode active material is relatively wide, and conventional positive electrode active materials in the art can be applied to the present invention, for example, the positive electrode active material can be a lithium iron phosphate positive electrode material and / or a ternary positive electrode material. Preferably, the ternary positive electrode material is selected from nickel cobalt aluminum oxide and / or nickel cobalt manganese oxide.

[0033] According to some preferred embodiments of the present invention, based on the total amount of effective components of the slurry, the content of the positive electrode active material is 90-98wt%, preferably 95-98wt%, the content of the first binder is 1-7wt%, preferably 1.2-3wt%; the total content of the second binder and the first conductive agent is 0.9-3.0wt%, preferably 0.9-2wt%.

[0034] In the present invention, the first binder is a fluorine-containing polyolefin binder, which is well known to those skilled in the art, and can be, for example, at least one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-propylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer and vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, preferably polyvinylidene fluoride.

[0035] In the present invention, the solvent includes the solvent introduced in each component or the preparation process. Preferably, the solvent includes a first solvent and a second solvent, and the first solvent and the second solvent may be the same or different; preferably, the first solvent and the second solvent are the same.

[0036] In the present invention, the selection range of the solvent is relatively wide, and it can be any organic solvent commonly used in positive electrode slurry in the art, as long as it can fully disperse the components in the positive electrode slurry.

[0037] According to some preferred embodiments of the present invention, the first solvent and the second solvent are each independently selected from N-methylpyrrolidone (NMP) and / or dimethylacetamide, preferably N-methylpyrrolidone.

[0038] In the present invention, the amount of the solvent is based on satisfying the solid content of the above-mentioned positive electrode slurry. Preferably, based on the total amount of the first binder and the first solvent, the content of the first binder is 4-7wt%, preferably 5-7wt%, and the content of the first solvent is 93-96wt%, preferably 93-95wt%.

[0039] Preferably, based on the total amount of the second binder, the second solvent and the first conductive agent, the content of the second binder is 10-30wt%, preferably 10-21wt%, the content of the second solvent is 25-55wt%, preferably 25-40wt%; the content of the first conductive agent is 15-65wt%, preferably 39-65wt%.

[0040] The present invention has no special requirements for the specific type of the second binder, as long as its molecular structure contains amino and hydroxyl groups. Preferably, the molecular weight of the second binder is ≤100000 g / mol, preferably 60-10000 g / mol. The use of a second binder with the above-mentioned preferred molecular weight is conducive to improving the solvent volatility during the coating process of the slurry, does not cause the binder to float, and improves the peel strength of the thick electrode.

[0041] According to some preferred embodiments of the present invention, the second binder has a structure as shown in formula (1):

[0042]

[0043] Wherein, each R1 in formula (1) may be the same or different, and each R1 is independently selected from a hydrogen atom or a substituted or unsubstituted C1-C6 hydrocarbon group; the substituent in the substituted C1-C6 hydrocarbon group is preferably a hydroxyl group and / or an amino group; preferably, each R1 is independently selected from any one of a hydrogen atom, a methyl group, an ethyl group, a propyl group, a hydroxymethyl group, a hydroxyethyl group and a hydroxypropyl group, and at least one R1 is not a hydrogen atom;

[0044] According to some particularly preferred embodiments of the present invention, the second binder is selected from at least one of 2-amino-2-methyl-1-propanol, 1-amino-2-methyl-2-propanol and 2-amino-1-butanol.

[0045] According to the present invention, preferably, the first conductive agent is a point-shaped conductive agent. Point-shaped conductive agents have a conventional definition in the art, referring to tiny spherical or quasi-spherical particles, which can minimize damage to the internal structure of the battery while increasing the contact area; similarly, in the following text, a linear conductive agent refers to a conductive material in a linear or fibrous form, and a planar conductive agent refers to a conductive material with a two-dimensional planar structure, which are all well known to those skilled in the art.

[0046] According to some preferred embodiments of the present invention, the first conductive agent is selected from at least one of acetylene black, Super-P and Ketjen black.

[0047] According to some preferred embodiments of the present invention, the slurry effective components further include a second conductive agent, and the second conductive agent is selected from a linear conductive agent and / or a planar conductive agent. In the above preferred case, it is conducive to the construction of a three-dimensional mesh conductive network, further improving the conductivity of the thick electrode, reducing the internal resistance, and reducing the heat generation of the battery cell.

[0048] Preferably, the linear conductive agent is selected from carbon nanotubes and / or carbon fibers.

[0049] Preferably, the planar conductive agent is selected from graphene and / or conductive graphite.

[0050] Preferably, based on the total amount of effective components of the slurry, the content of the second conductive agent is 0-1.2 wt %, preferably 0.1-0.7 wt %.

[0051] According to some preferred embodiments of the present invention, the second conductive agent includes a linear conductive agent and a planar conductive agent, and the mass ratio of the linear conductive agent to the planar conductive agent is (1-3): 1, preferably (1-2.5): 1. The use of the above preferred second conductive agent composition is conducive to constructing a three-dimensional conductive network and further improving the electrochemical performance of the obtained battery cell.

[0052] According to some preferred embodiments of the present invention, the effective components of the slurry also include a solid electrolyte. The above preferred embodiments are beneficial to improving the safety performance of the battery cell while ensuring the high energy density of the battery cell. Preferably, the solid electrolyte is selected from at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide and lithium lanthanum titanium oxide.

[0053] According to the present invention, preferably, based on the total amount of effective components of the slurry, the content of the solid electrolyte is 0-5wt%, preferably 1-3wt%.

[0054] According to some preferred embodiments of the present invention, the positive electrode slurry further includes a lithium supplement additive. Any conventional lithium supplement additive in the art can be applied to the present invention, and preferably, the lithium supplement additive is selected from at least one of lithium ferrite, lithium nickelate and lithium oxalate.

[0055] Preferably, based on the total amount of effective components of the slurry, the content of the lithium supplement additive is 0-5wt%, preferably 0.5-3wt%. In the above preferred case, the synergistic effect of the lithium supplement additive and other components in the positive electrode slurry is conducive to reducing the surface density under the condition of achieving the same capacity, and can also increase the capacity of the battery cell under the same surface density.

[0056] According to some particularly preferred embodiments of the present invention, the positive electrode slurry is composed of a slurry effective component and a solvent, and the slurry effective component is composed of a positive electrode active material, a first binder, a second binder, a first conductive agent, and a second conductive agent; wherein the first binder is a fluorinated polyolefin binder, the second binder is a compound containing amino and hydroxyl groups, the first conductive agent is a point conductive agent, and the second conductive agent includes a linear conductive agent and a planar conductive agent. Preferably, based on the total amount of the slurry effective components, the content of the positive electrode active material is 95-98wt%, the content of the first binder is 1.2-3wt%, the total content of the second binder and the first conductive agent is 0.9-3wt%, and the content of the second conductive agent is 0-0.7wt%.

[0057] The present invention has no particular limitation on the homogenization method of the positive electrode slurry. As long as the positive electrode slurry has the above-mentioned composition and physicochemical characteristics, those skilled in the art can prepare it by conventional methods in the art.

[0058] Preferably, the second aspect of the present invention provides a method for preparing the above-mentioned positive electrode slurry, comprising:

[0059] (1) dissolving a first binder in a first solvent to obtain a first adhesive solution;

[0060] (2) mixing a second binder, a second solvent and a first conductive agent to obtain a second adhesive solution;

[0061] Wherein, the first binder is a fluorinated polyolefin binder, and the second binder is a compound containing amino groups and hydroxyl groups;

[0062] (3) Mixing the first slurry, the second slurry and the positive electrode active material.

[0063] In the present invention, the first glue and the second glue are prepared separately, and then the first glue, the second glue and the positive electrode active material are mixed. The positive electrode slurry prepared by the above-mentioned homogenization method can improve the conductivity and peel strength while improving the performance of the battery cell. The reason may be that the first conductive agent, the second solvent and the second binder are first mixed to obtain the second glue, which can make the first conductive agent disperse more evenly, and the particles in the positive electrode slurry prepared are further dispersed more evenly, which weakens the Brownian motion of the particles in the slurry, making the slurry more stable, and being able to obtain a positive electrode slurry with a suitable solid content and viscosity, which is conducive to improving the stability of the coating surface density.

[0064] In the present invention, the selection ranges of the first binder, the second binder, the first solvent, the second solvent and the first conductive agent are the same as those in the first aspect and will not be described in detail herein.

[0065] According to the present invention, preferably, in step (2), the mixing is carried out under stirring conditions, with a stirring rate of 1500-2000 rpm and a stirring time of 30-35 min.

[0066] According to some preferred embodiments of the present invention, step (3) includes step (3-1), step (3-2) and step (3-3):

[0067] (3-1) performing a first mixing of the first glue solution and the second glue solution;

[0068] (3-2) adding a second conductive agent to the mixture obtained by the first mixing to perform a second mixing;

[0069] (3-3) The positive electrode active material is added to the mixture obtained by the second mixing, and the third mixing is performed.

[0070] The above-mentioned preferred embodiment is beneficial to dispersing the point-shaped conductive agent and the second binder, making the point-shaped conductive agent dispersed more evenly. Adding the second glue makes the particles inside the slurry dispersed more evenly, weakening the Brownian motion of the particles in the slurry, making the slurry more stable, and is beneficial to more stable coating surface density.

[0071] The present invention has no particular requirements for the specific conditions of the first mixing and the second mixing, as long as the components can be mixed uniformly. Preferably, the first mixing and the second mixing are performed under stirring conditions, and the stirring rate of the second mixing is higher than the stirring rate of the first mixing, and the stirring rate of the third mixing is higher than the stirring rate of the second mixing.

[0072] Preferably, the conditions for the first mixing include: a stirring rate of 1500-2000 rpm, and a stirring time of 30-35 min.

[0073] Preferably, the second mixing conditions include: a stirring rate of 2500-3500 rpm and a stirring time of 30-35 min.

[0074] Preferably, the conditions of the third mixing include: a stirring rate of 4000-4500 rpm, and a stirring time of 30-35 min.

[0075] The use of the above preferred mixing conditions can further improve the homogenization effect and help improve the dispersibility of the slurry.

[0076] According to the present invention, preferably, the preparation method further comprises an optional step (4), which comprises: mixing the mixture obtained in step (3) with a solid electrolyte and / or a lithium supplement additive. The present invention does not particularly limit the mixing conditions in step (4), and those skilled in the art can select according to actual needs. Preferably, the mixing conditions can be the same as the third mixing conditions.

[0077] The present invention further provides a method for preparing a positive electrode slurry, comprising:

[0078] Step (1) dissolving a first binder in a first solvent to obtain a first adhesive solution;

[0079] Step (2) mixing the second binder, the second solvent and the first conductive agent to obtain a second adhesive solution;

[0080] Wherein, the first binder is a fluorinated polyolefin binder, the second binder is a compound containing amino groups and hydroxyl groups; the first conductive agent is a dot conductive agent;

[0081] Step (3) includes:

[0082] (3-1) performing a first mixing of the first glue solution and the second glue solution;

[0083] Preferably, the first mixing conditions include: a stirring rate of 1500-2000 rpm and a stirring time of 30-35 min;

[0084] (3-2) adding a second conductive agent to the mixture obtained by the first mixing to perform a second mixing;

[0085] Wherein, the second conductive agent is selected from a linear conductive agent and / or a planar conductive agent;

[0086] Preferably, the second mixing conditions include: a stirring rate of 2500-3500 rpm and a stirring time of 30-35 min;

[0087] (3-3) adding a positive electrode active material to the mixture obtained by the second mixing to perform a third mixing;

[0088] Preferably, the third mixing conditions include: a stirring rate of 4000-4500 rpm and a stirring time of 30-35 min;

[0089] Step (4) mixing the mixture obtained in step (3) with a solid electrolyte and / or a lithium supplement additive.

[0090] A third aspect of the present invention provides a positive electrode plate, comprising a current collector and an active coating layer disposed on the surface of the current collector, wherein the active coating layer is made of the positive electrode slurry described in the first aspect.

[0091] According to the present invention, compared with the prior art, the positive electrode sheet provided by the present invention has a higher peel strength. Preferably, the peel strength of the positive electrode sheet is 30-60N / m, preferably 35-60N / m. The reason may be that under the synergistic effect of the first glue and the second glue, the solid content and viscosity of the positive electrode slurry are controlled to meet the above range, which can increase the volatility of the solvent during the coating process and avoid the floating of the binder, thereby improving the peel strength of the sheet.

[0092] In the present invention, the method for testing the peel strength of the pole piece includes: cleaning the sample steel plate until the working surface of the steel plate is visually clean, cutting the pole piece to be tested into a width of 20 mm and a length ≥ 120 mm to obtain a pole piece sample to be tested. Cut a 20mm wide 3M tape to a length of 50mm, stick the cut tape on the steel plate along the edge of one side of the long steel plate, and stick and fix the electrode sample to be tested along the tape sticking direction, fold the unsticked end of the sample 180° along the end of the tape, and peel 5mm between the material area and the current collector, adjust the position of the fixture, fix the lower end of the steel plate at the lower fixture position of the tensile testing machine, fix the unsticked end of the sample at the upper fixture position of the tensile testing machine, adjust the setting rings of the upper and lower limit safety switches and tighten them, open the "TM2101" software, clear the experimental force, deformation, and displacement, set the tensile testing machine speed to 300±10mm / min, click the test start button to start the test, and stop automatically when the sample is broken or until the electrode is completely separated from the steel plate. Stop the test and click "End Test", test 3 times in a row, and record the test results.

[0093] The present invention does not particularly limit the type of the current collector, and any current collector known in the art that can be used for the positive electrode sheet can be applied to the present invention. Preferably, the current collector is selected from aluminum foil or aluminum-plated current collector, and the aluminum foil can be plain foil (uncoated) or coated foil, and the coated foil can be, for example, carbon-coated aluminum foil and / or aluminum foil coated with a polymer current collector. The present invention also does not particularly limit the source of the current collector, which can be purchased commercially or prepared by any method known in the art. Preferably, the thickness of the current collector is 12-14 μm.

[0094] According to the present invention, preferably, the current collector has a first surface and a second surface facing each other, and the active coating layer is disposed on the first surface and / or the second surface. It is understandable that the current collector may be coated with an active coating layer on one side or on both sides, and the present invention has no particular limitation on this, and those skilled in the art may make a selection according to actual needs.

[0095] According to some preferred embodiments of the present invention, the active coating layer is disposed on the first surface and the second surface, respectively. The thickness of the active coating layer disposed on the first surface and the second surface may be the same or different, and preferably, the thickness of the active coating layer is the same.

[0096] Preferably, the thickness of the active coating layer is 70-160 μm. It is understood that the thickness of the active coating layer in the present invention refers to the thickness of the active coating layer on the surface of any side of the current collector.

[0097] According to some preferred embodiments of the present invention, the positive electrode active material in the positive electrode slurry is a lithium iron phosphate positive electrode material, and the single-sided surface density of the positive electrode sheet is 240-300 g / m 2 , compacted density is 2-2.7g / cm 3 .

[0098] Preferably, active coating layers are provided on the first surface and the second surface respectively, and the thickness of the active coating layers is 70-160 μm respectively.

[0099] According to some other preferred embodiments of the present invention, the positive electrode active material in the positive electrode slurry is a ternary positive electrode material, and the single-sided surface density of the positive electrode sheet is 290-320 g / m 2 , compacted density is 3.2-3.7g / cm 3 .

[0100] Preferably, active coating layers are provided on the first surface and the second surface respectively, and the thickness of the active coating layers is 70-100 μm respectively.

[0101] In the present invention, the test method of the surface density includes: using a sampler to take samples of the same shape and area on the dried pole piece and the uncoated current collector, respectively, and record them as m1 and m2; placing m1 and m2 in a tray and baking them in a 110°C oven for 2 minutes, then placing m1 and m2 to room temperature, and using an electronic balance to weigh the mass of m1 and m2 respectively, and subtracting the mass of m2 from m1 and dividing it by the area of ​​the sample to obtain the pole piece surface density. Measure and calculate the surface density of 5 sampled samples respectively, and take the average value as the surface density of the pole piece.

[0102] A fourth aspect of the present invention provides a method for preparing a positive electrode sheet, comprising: coating the positive electrode slurry described in the first aspect on the surface of a current collector, and then drying and rolling.

[0103] According to the present invention, preferably, the number of coatings is 1. The cathode slurry provided by the present invention can be used to prepare a thick electrode by coating once, which is compatible with the existing single-layer coating technology and reduces costs. The electrical performance of the thick electrode sheet produced by the present invention is equivalent to that of the electrode sheet produced by the thin electrode technology, and the gram capacity is equivalent, reaching the technical level of the thin electrode.

[0104] The present invention has no particular limitation on the coating method, and the coating can be carried out in a conventional manner in the art, and those skilled in the art can select the coating method according to actual needs. Preferably, the coating method is any one of extrusion coating, blade coating and transfer coating, preferably extrusion coating.

[0105] According to the present invention, preferably, the coating speed is 4-6 m / min.

[0106] According to some preferred embodiments of the present invention, the drying temperature is 70-110° C. The drying can be performed by programmed temperature increase, which is not particularly limited in the present invention and can be performed by conventional operation methods in the art.

[0107] The present invention has no particular limitation on the specific operating conditions of the roller pressing. Preferably, the pressure of the roller pressing is not higher than 100T, preferably 50-80T.

[0108] A fifth aspect of the present invention provides a lithium-ion battery, comprising the positive electrode sheet described in the third aspect or the positive electrode sheet prepared by the preparation method described in the fourth aspect.

[0109] The present invention will be described in detail below through examples.

[0110] In the following examples, unless otherwise specified, the raw materials used were commercially available.

[0111] PVDF was purchased from Solvay 5130.

[0112] SP is purchased from Temigo.

[0113] Carbon nanotubes and graphene are purchased from Xianfeng Nano.

[0114] Lithium iron phosphate is purchased from Defang Nano.

[0115] The ternary NCM811 is purchased from Xiatung.

[0116] Example 1

[0117] 373.83 g of PVDF was dissolved in 6768.53 g of NMP to obtain a first glue solution; 83.07 g of 2-amino-2-methyl-1-propanol, 154.28 g of NMP and 166.15 g of SP were mixed to obtain a second glue solution.

[0118] The first glue solution and the second glue solution were mixed for the first time, stirred for 30 minutes at a stirring speed of 2000 rpm; then 101.77 g of carbon nanotubes and 43.61 g of graphene were added for the second mixing, stirred for 35 minutes at a stirring speed of 3500 rpm; finally 20000 g of lithium iron phosphate was added for the third mixing, stirred for 35 minutes at a stirring speed of 4500 rpm. After homogenization, a positive electrode slurry was obtained, which was recorded as A1.

[0119] The slurry viscosity, solid content and cone penetration were tested, and the results are shown in Table 1.

[0120] The slurry was applied to the carbon-coated aluminum foil (aluminum foil thickness 12 μm, carbon layer thickness 1 μm on the upper and lower surfaces) by extrusion coating machine, the coating speed was 5 m / min, the drying temperature was 80 ° C, and the electrode was coated and rolled with 64T pressure to obtain the positive electrode P1. Figure 1 As shown, it can be seen that the surface of the pole piece is smooth and flat without cracking. The thickness and surface density of the pole piece are shown in Table 2.

[0121] The negative electrode is graphite, the electrolyte is a commercially available electrolyte, the electrolyte lithium salt is LiPF6 (1 mol / L), and the solvent volume ratio is dimethyl carbonate (DMC): ethyl methyl carbonate (EMC): ethylene carbonate (EC): diethyl carbonate (DEC) = 1:1:1:1. The square shell winding method is adopted for assembly, liquid injection, formation, and then the electrochemical performance test is carried out. The test conditions include:

[0122] 1) Connect the battery cell to the test instrument and let it stand for 10 minutes; 2) Charge to 3.65V at 0.5P constant power and let it stand for 10 minutes; 3) Discharge to 2.5V at 0.5P constant power; Steps 2)-3) are one cycle, and the cycle is repeated 3 times. The charging capacity, discharge capacity, charging energy, and discharge energy of each cycle are recorded, and their average values ​​are calculated to obtain the mass energy density and volume energy density. The results of mass energy retention rate and volume energy retention rate are shown in Table 3.

[0123] Example 2

[0124] The method of Example 1 was followed, except that NCM811 of equal mass was used to replace lithium iron phosphate, and the obtained positive electrode slurry was recorded as A2. The slurry viscosity, solid content and cone penetration were tested, and the results are shown in Table 1.

[0125] A positive electrode sheet was prepared according to the method of Example 1, and the prepared sheet was recorded as P2. The thickness and surface density of the sheet are shown in Table 2.

[0126] The battery cells were assembled in the manner of Example 1 and the electrical performance was evaluated. The results are shown in Table 3.

[0127] Example 3

[0128] 373.06 g of PVDF was dissolved in 6831.48 g of NMP to obtain a first glue solution; 41.45 g of 2-amino-2-methyl-1-propanol, 76.98 g of NMP and 165.80 g of SP were mixed to obtain a second glue solution.

[0129] The first glue solution and the second glue solution were mixed for the first time, stirred for 30 minutes at a stirring speed of 2000 rpm; then 101.55 g of carbon nanotubes and 43.52 g of graphene were added for the second time, stirred for 35 minutes at a stirring speed of 3500 rpm; finally 20000 g of lithium iron phosphate was added for the third time, stirred for 35 minutes at a stirring speed of 4500 rpm. After homogenization, the obtained positive electrode slurry was recorded as A3.

[0130] The slurry viscosity, solid content and cone penetration were tested, and the results are shown in Table 1.

[0131] A positive electrode sheet was prepared according to the method of Example 1, and the prepared sheet was recorded as P3. The thickness and surface density of the sheet are shown in Table 2.

[0132] The battery cells were assembled according to the method of Example 1 and the electrical performance was evaluated. The results are shown in Table 3.

[0133] Example 4

[0134] 376.18 g of PVDF was dissolved in 6578.10 g of NMP to obtain a first glue solution; 208.98 g of 2-amino-2-methyl-1-propanol, 388.12 g of NMP and 167.19 g of SP were mixed to obtain a second glue solution.

[0135] The first glue solution and the second glue solution were mixed for the first time, stirred for 30 minutes at a stirring speed of 2000 rpm; then 102.40 g of carbon nanotubes and 43.89 g of graphene were added for the second mixing, stirred for 35 minutes at a stirring speed of 3500 rpm; finally 20000 g of lithium iron phosphate was added for the third mixing, stirred for 35 minutes at a stirring speed of 4500 rpm. After homogenization, the obtained positive electrode slurry was recorded as A4.

[0136] The slurry viscosity, solid content and cone penetration were tested, and the results are shown in Table 1.

[0137] A positive electrode sheet was prepared according to the method of Example 1, and the prepared sheet was recorded as P4. The thickness and surface density of the sheet are shown in Table 2.

[0138] The battery was assembled according to the method of Example 1 and the electrical performance was evaluated. The results are shown in Table 3.

[0139] Example 5

[0140] The method of Example 1 was followed, except that an equal amount of 1-amino-2-methyl-2-propanol was used to replace 2-amino-2-methyl-1-propanol.

[0141] The obtained positive electrode slurry was recorded as A5. The viscosity, solid content and cone penetration of the slurry were tested, and the results are shown in Table 1.

[0142] A positive electrode sheet was prepared according to the method of Example 1, and the prepared sheet was recorded as P5. The thickness and surface density of the sheet are shown in Table 2.

[0143] The battery cells were assembled according to the method of Example 1 and the electrical performance was evaluated. The results are shown in Table 3.

[0144] Example 6

[0145] 373.83 g of PVDF was dissolved in 6768.53 g of NMP to obtain a first glue solution; 83.07 g of 2-amino-2-methyl-1-propanol, 154.28 g of NMP and 166.15 g of SP were mixed to obtain a second glue solution.

[0146] The first glue solution and the second glue solution were mixed for the first time, stirred for 30 minutes at a stirring speed of 2000rpm; then 101.77g carbon nanotubes and 43.61g graphene were added for the second mixing, stirred for 35 minutes at a stirring speed of 3500rpm; then 19500g lithium iron phosphate was added for the third mixing, stirred for 35 minutes at a stirring speed of 45000rpm; finally 500g lithium oxalate was added, stirred for 35 minutes at a stirring speed of 45000rpm. After homogenization, a positive electrode slurry was obtained, which was recorded as A6. The slurry viscosity, solid content and cone penetration were tested, and the results are shown in Table 1.

[0147] A positive electrode sheet was prepared according to the method of Example 1, and the prepared sheet was recorded as P6. The thickness and surface density of the sheet are shown in Table 2.

[0148] The battery cells were assembled according to the method of Example 1 and the electrical performance was evaluated. The results are shown in Table 3.

[0149] Example 7

[0150] 378.95 g of PVDF was dissolved in 6861.15 g of NMP to obtain a first glue solution; 84.21 g of 2-amino-2-methyl-1-propanol, 156.39 g of NMP and 168.42 g of SP were mixed to obtain a second glue solution.

[0151] The first glue solution and the second glue solution were mixed for the first time, stirred for 30 minutes at a stirring speed of 2000rpm; then 73.68g of carbon nanotubes and 31.58g of graphene were added for the second mixing, stirred for 35 minutes at a stirring speed of 3500rpm; then 20000g of lithium iron phosphate was added for the third mixing, stirred for 35 minutes at a stirring speed of 45000rpm; finally 315.79g of LATP was added, stirred for 35 minutes at a stirring speed of 45000rpm. After homogenization, a positive electrode slurry was obtained, which was recorded as A7. The slurry viscosity, solid content and cone penetration were tested, and the results are shown in Table 1.

[0152] A positive electrode sheet was prepared according to the method of Example 1, and the prepared sheet was recorded as P7. The thickness and surface density of the sheet are shown in Table 2.

[0153] The battery cells were assembled according to the method of Example 1 and the electrical performance was evaluated. The results are shown in Table 3.

[0154] Example 8

[0155] 373.83g PVDF was dissolved in 6922.81g NMP and 83.07g 2-amino-2-methyl-1-propanol to obtain a glue solution. The glue solution was first mixed with 166.15g SP and stirred for 30min at a stirring speed of 2000rpm; then 101.77g carbon nanotubes and 43.61g graphene were added for a second mixing and stirred for 35min at a stirring speed of 3500rpm; finally, 20000g lithium iron phosphate was added for a third mixing and stirred for 35min at a stirring speed of 45000rpm. After homogenization, a positive electrode slurry was obtained, which was recorded as A8.

[0156] The slurry viscosity, solid content and cone penetration were tested, and the results are shown in Table 1.

[0157] A positive electrode sheet was prepared according to the method of Example 1, and the prepared sheet was recorded as P8. The thickness and surface density of the sheet are shown in Table 2.

[0158] The battery cells were assembled according to the method of Example 1 and the electrical performance was evaluated. The results are shown in Table 3.

[0159] Example 9

[0160] 371.13 g of PVDF was dissolved in 6719.69 g of NMP to obtain a first glue solution; 82.47 g of 2-amino-2-methyl-1-propanol, 153.17 g of NMP and 164.95 g of SP were mixed to obtain a second glue solution.

[0161] The first glue solution and the second glue solution were mixed for the first time, stirred for 30 minutes at a stirring speed of 2000 rpm; finally, 20000 g of lithium iron phosphate was added for the third mixing, stirred for 35 minutes at a stirring speed of 4500 rpm. After homogenization, a positive electrode slurry was obtained, which was recorded as A9.

[0162] The slurry viscosity, solid content and cone penetration were tested, and the results are shown in Table 1.

[0163] A positive electrode sheet was prepared according to the method of Example 1, and the prepared sheet was recorded as P9. The thickness and surface density of the sheet are shown in Table 2.

[0164] The battery cells were assembled according to the method of Example 1 and the electrical performance was evaluated. The results are shown in Table 3.

[0165] Example 10

[0166] The homogenization was carried out in the same manner as in Example 1, except that 373.83 g of PVDF was dissolved in 8746.48 g of NMP to complete the homogenization, thereby obtaining a positive electrode slurry, which was recorded as A10.

[0167] The slurry viscosity, solid content and cone penetration were tested, and the results are shown in Table 1.

[0168] A positive electrode sheet was prepared according to the method of Example 1, and the prepared sheet was recorded as P10. The thickness and surface density of the sheet are shown in Table 2.

[0169] The battery cells were assembled according to the method of Example 1 and the electrical performance was evaluated. The results are shown in Table 3.

[0170] Embodiment 11

[0171] The homogenization was carried out in the same manner as in Example 1, except that 373.83 g of PVDF was dissolved in 5703.38 g of NMP to complete the homogenization, thereby obtaining a positive electrode slurry, which was recorded as A11.

[0172] The slurry viscosity, solid content and cone penetration were tested, and the results are shown in Table 1.

[0173] A positive electrode sheet was prepared according to the method of Example 1, and the prepared sheet was recorded as P11. The thickness and surface density of the sheet are shown in Table 2.

[0174] The battery cells were assembled according to the method of Example 1 and the electrical performance was evaluated. The results are shown in Table 3.

[0175] Comparative Example 1

[0176] 372.29g PVDF was dissolved in 12676.39g NMP, and 165.46g SP was added and mixed, stirred for 30min at a stirring speed of 1500rpm, and then 101.34g carbon nanotubes and 43.43g graphene were added, stirred for 30min at a stirring speed of 2500rpm, and finally 20000g lithium iron phosphate was added, stirred for 35min at a stirring speed of 4500rpm. The positive electrode slurry was obtained and recorded as DA1. The slurry viscosity, solid content and cone penetration were tested, and the results are shown in Table 1.

[0177] The positive electrode sheet was prepared according to the method of Example 1. The positive electrode slurry can only be coated with a low surface density electrode sheet, and the surface density coating is 192g / m 2 The pole piece has a complete and smooth appearance, and the pole piece is recorded as DP1. When the pole piece surface density is higher than 216g / m 2 , the pole piece cracks and cannot be coated. .

[0178] According to the method of Example 1, the coating surface density is 190g / m 2 The electrode pieces were assembled into battery cells and the electrical performance was evaluated. The results are shown in Table 3.

[0179] Comparative Example 2

[0180] The slurry was homogenized in accordance with the method of Comparative Example 1, except that the amount of NMP used was changed to 6894.17 g. A positive electrode slurry was obtained, which was recorded as DA2. The slurry viscosity, solid content and cone penetration were tested, and the results are shown in Table 1.

[0181] A positive electrode sheet was prepared according to the method of Example 1, and the prepared electrode sheet was recorded as DP2. Figure 2 As shown, it can be seen that the coating surface density of the pole piece coating process is 300g / m 2 The electrode has serious cracking and cannot be tested for peel strength. The thickness and surface density of the electrode are shown in Table 2.

[0182] The battery cell cannot be assembled due to severe cracking of the electrode.

[0183] Comparative Example 3

[0184] The method of Example 1 was followed, except that 41.54 g of vinyl alcohol and 41.54 g of ethylenediamine were used instead of 2-amino-2-methyl-1-propanol.

[0185] The positive electrode slurry was obtained and recorded as DA3. The viscosity, solid content and cone penetration of the slurry were tested, and the results are shown in Table 1.

[0186] A positive electrode sheet was prepared according to the method of Example 1, and the prepared sheet was recorded as DP3. The thickness and surface density of the sheet are shown in Table 2.

[0187] The battery cells were assembled according to the method of Example 1 and the electrical performance was evaluated. The results are shown in Table 3.

[0188] Table 1

[0189]

[0190]

[0191] Table 2

[0192]

[0193]

[0194] Table 3

[0195] serial number Mass energy density Wh / kg Volume energy density Wh / L Example 1 190.1 449.8 Example 2 310.3 579.6 Example 3 186.9 441.4 Example 4 184.1 433.8 Example 5 186.4 438.6 Example 6 187.7 438.2 Example 7 182.6 431.9 Example 8 186.2 436.7 Example 9 184.9 431.4 Example 10 183.7 431.7 Embodiment 11 187.8 444.8 Comparative Example 1 176.3 417.8 Comparative Example 3 180.6 427.1

[0196] It can be seen from the results in Table 2 and Table 3 that the electrode sheet made by using the positive electrode slurry provided by the present invention can take into account both high peel strength and surface density, further improve the electrochemical performance of the battery cell, and have high mass energy density and volume energy density.

[0197] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A positive electrode slurry, characterized in that: The positive electrode slurry comprises a slurry effective component and a solvent, wherein the slurry effective component comprises a positive electrode active material, a first binder, a second binder and a first conductive agent; Wherein, the first binder is a fluorinated polyolefin binder; the second binder is a compound containing amino groups and hydroxyl groups; The solid content of the positive electrode slurry is not less than 68%, and the viscosity at 25±2° C. is not less than 100,000 mPa·S.

2. The positive electrode slurry according to claim 1, wherein The solid content of the positive electrode slurry is 68-85%, preferably 72-78%; Preferably, the viscosity of the positive electrode slurry at 25±2°C is 100000-400000 mPa·S, preferably 120000-200000 mPa·S; Preferably, the cone penetration of the positive electrode slurry is not less than 30 mm, preferably 30-50 mm, and more preferably 32-37 mm.

3. The positive electrode slurry according to claim 1 or 2, wherein: The positive electrode active material is selected from lithium iron phosphate positive electrode material and / or ternary positive electrode material; preferably, the ternary positive electrode material is selected from nickel cobalt aluminum oxide and / or nickel cobalt manganese oxide; Preferably, based on the total amount of effective components of the slurry, the content of the positive electrode active material is 90-98wt%, preferably 95-98wt%, the content of the first binder is 1-7wt%, preferably 1.2-3wt%; the total content of the second binder and the first conductive agent is 0.9-3wt%, preferably 0.9-2wt%; Preferably, the first binder is selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-propylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer and vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer.

4. The positive electrode slurry according to any one of claims 1 to 3, wherein: The molecular weight of the second binder is ≤100000 g / mol, preferably 60-10000 g / mol; Preferably, the second binder has a structure as shown in formula (1), Base; In the description, replace each RC 1 1- Each C6 hydrocarbon group is independently selected from a hydrogen atom, a methyl group, an ethyl group, a propyl group, a hydroxymethyl group, a hydroxyethyl group and a hydroxypropyl group, and at least one R1 is not a hydrogen atom; Preferably, the first conductive agent is a dot-shaped conductive agent, preferably at least one of acetylene black, Super-P and Ketjen black.

5. The positive electrode slurry according to any one of claims 1 to 4, wherein: The solvent comprises a first solvent and a second solvent, wherein the first solvent and the second solvent are each independently selected from N-methylpyrrolidone and / or dimethylacetamide; Preferably, based on the total amount of the first binder and the first solvent, the content of the first binder is 4-7wt%, and the content of the first solvent is 93-96wt%; Preferably, based on the total amount of the second binder, the second solvent and the first conductive agent, the content of the second binder is 10-30wt%, preferably 10-21wt%, the content of the second solvent is 25-55wt%, preferably 25-40wt%; the content of the first conductive agent is 15-65wt%, preferably 39-65wt%.

6. The positive electrode slurry according to any one of claims 1 to 5, wherein: The effective components of the slurry also include a second conductive agent, which is selected from a linear conductive agent and / or a planar conductive agent; Preferably, the linear conductive agent is selected from at least one of carbon nanotubes, carbon fibers and silver nanowires; Preferably, the planar conductive agent is selected from graphene and / or conductive graphite; Preferably, based on the total amount of effective components of the slurry, the content of the second conductive agent is 0-1.2wt%, preferably 0.1-0.7wt%; Preferably, the second conductive agent includes a linear conductive agent and a planar conductive agent, and the mass ratio of the linear conductive agent to the planar conductive agent is (1-3):1; Preferably, the slurry effective components also include a solid electrolyte; Preferably, the solid electrolyte is selected from at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide and lithium lanthanum titanium oxide; Preferably, based on the total amount of effective components of the slurry, the content of the solid electrolyte is 0-5wt%, preferably 1-3wt%; Preferably, the effective components of the slurry also include a lithium supplement additive; Preferably, the lithium supplement additive is selected from at least one of lithium ferrite, lithium nickelate and lithium oxalate; Preferably, based on the total amount of effective components of the slurry, the content of the lithium supplement additive is 0-5wt%, preferably 0.5-3wt%.

7. The method for preparing the positive electrode slurry according to any one of claims 1 to 6, comprising: (1) The solvent includes a first solvent and a second solvent, and the first binder is dissolved in the first solvent to obtain a first adhesive solution; (2) mixing a second binder, a second solvent and a first conductive agent to obtain a second adhesive solution; Wherein, the first binder is a fluorinated polyolefin binder, and the second binder is a compound containing amino groups and hydroxyl groups; (3) Mixing the first slurry, the second slurry and the positive electrode active material.

8. The preparation method according to claim 7, wherein: In step (2), the mixing is carried out under stirring conditions, the stirring rate is 1500-2000 rpm, and the stirring time is 30-35 min; Preferably, step (3) includes step (3-1), step (3-2) and step (3-3): (3-1) performing a first mixing of the first glue solution and the second glue solution; (3-2) adding a second conductive agent to the mixture obtained by the first mixing to perform a second mixing; (3-3) adding a positive electrode active material to the mixture obtained by the second mixing to perform a third mixing; Preferably, the first mixing, the second mixing and the third mixing are performed under stirring conditions, and the stirring rate of the second mixing is higher than the stirring rate of the first mixing, and the stirring rate of the third mixing is higher than the stirring rate of the second mixing; Preferably, the first mixing conditions include: a stirring rate of 1500-2000 rpm and a stirring time of 30-35 min; Preferably, the second mixing conditions include: a stirring rate of 2500-3500 rpm and a stirring time of 30-35 min; Preferably, the third mixing conditions include: a stirring rate of 4000-4500 rpm and a stirring time of 30-35 min; Preferably, the preparation method further comprises an optional step (4), which comprises: mixing the mixture obtained in step (3) with a solid electrolyte and / or a lithium supplement additive; Preferably, the first solvent and the second solvent are each independently selected from N-methylpyrrolidone and / or dimethylacetamide.

9. A positive electrode sheet, comprising a current collector and an active coating layer disposed on the surface of the current collector, wherein: The active coating layer is made of the positive electrode slurry according to any one of claims 1 to 6; Preferably, the peel strength of the positive electrode sheet is 30-60N / m; Preferably, the current collector is selected from aluminum foil or aluminum-plated current collector; Preferably, the thickness of the current collector is 12-14 μm; Preferably, the current collector has a first surface and a second surface facing each other, and the active coating layer is disposed on the first surface and / or the second surface; Preferably, the active coating layer is disposed on the first surface and the second surface respectively, and the thickness of the active coating layer is 70-160 μm.

10. The positive electrode sheet according to claim 9, wherein: The positive electrode active material in the positive electrode slurry is a lithium iron phosphate positive electrode material, and the single-sided surface density of the positive electrode sheet is 240-300 g / m 2 , compacted density is 2-2.7g / cm 3 ; Preferably, active coating layers are provided on the first surface and the second surface respectively, and the thickness of the active coating layers is 70-160 μm respectively.

11. The positive electrode sheet according to claim 9, wherein: The positive electrode active material in the positive electrode slurry is a ternary positive electrode material, and the single-sided surface density of the positive electrode sheet is 290-320 g / m 2 , compacted density is 3.2-3.7g / cm 3 ; Preferably, active coating layers are provided on the first surface and the second surface respectively, and the thickness of the active coating layers is 70-100 μm respectively.

12. A method for preparing a positive electrode sheet, comprising: The positive electrode slurry according to any one of claims 1 to 6 is coated on the surface of the current collector, and then dried and roll-pressed.

13. The method for preparing a positive electrode sheet according to claim 12, wherein: The number of times of coating is 1 time; Preferably, the coating method is any one of extrusion coating, blade coating and transfer coating, preferably extrusion coating; Preferably, the coating speed is 4-6 m / min; Preferably, the drying temperature is 70-110°C; Preferably, the rolling pressure is not higher than 100T, preferably 50-80T.

14. A lithium ion battery, characterized in that: The invention comprises the positive electrode sheet described in any one of claims 9 to 11 or the positive electrode sheet prepared by the preparation method described in claim 12 or 13.